In silico Exploration of Inhibitors for SARS-CoV-2's Papain-Like Protease - Huynh, Tien; Cornell, Wendy; Luan, Binquan (Frontiers in Chemistry, 2021)
Coronavirus disease 2019 (COVID-19) is an ongoing global pandemic with very limited antiviral treatment. The disease is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), with very limited treatments so far. Demonstrated with good druggability, two major proteases of SARS-CoV-2, namely main protease (Mpro) and papain-like protease (PLpro) that are essential for viral maturation, have become the targets for many newly designed inhibitors. Unlike Mpro that have been heavily investigated, PLpro is not well studied so far. Here, we carried out the in silico high-throughput screening of all FDA-approved drugs via. the flexible docking simulation for potential inhibitors of PLpro and explored the molecular mechanism of binding between a known inhibitor rac5c and PLpro. Our results from molecular dynamics simulation show that the chance of drug repurposing for PLpro might be scarce. On the other hand, our long (about 450 ns) MD simulation confirms that rac5c can be bound stably inside the substrate-binding site of PLpro and unveils the molecular mechanism of binding for the rac5c-PLpro complex. The later may help perform further structural optimization and design more efficacious drugs for inhibiting PLpro.